High resolution modelling of the North Icelandic Irminger Current (NIIC) - K. Logemann; I. Harms (Copernicus Publications, 2006)
The northward inflow of Atlantic Water through Denmark Strait – the North Icelandic Irminger Current (NIIC) – is simulated with a numerical model of the North Atlantic and Arctic Ocean. The model uses the technique of adaptive grid refinement which allows a high spatial resolution (1 km horizontal, 10 m vertical) around Iceland. The model is used to assess time and space variability of volume and heat fluxes for the years 1997–2003. Passive tracers are applied to study origin and composition of NIIC water masses. The NIIC originates from two sources: the Irminger Current, flowing as part of the sub-polar gyre in 100–500 m depth along the Reykjanes Ridge and the shallow Icelandic coastal current, flowing north-westward on the south-west Icelandic shelf. The ratio of volume flux between the deep and shallow branch is around 2:1. The NIIC continues as a warm and saline branch northward through Denmark Strait where it entrains large amounts of polar water due to the collision with the southward flowing East Greenland Current. After passing Denmark Strait, the NIIC follows the coast line eastward being an important heat source for north Icelandic waters. At least 60% of the temporal temperature variability of north Icelandic waters is caused by the NIIC. The NIIC volume and heat transport is highly variable and depends strongly on the wind field north-east of Denmark Strait. Daily means can change from 1 Sv eastward to 2 Sv westward within a few days. Highest monthly mean transport rates occur in summer when winds from north are weak, whereas the volume flux is reduced by around 50% in winter. Summer heat flux rates can be even three times higher than in winter. The simulation also shows variability on the interannual scale. In particular weak winds from north during winter 2002/2003 combined with mild weather conditions south of Iceland led to anomalous high NIIC volume (+40%) and heat flux (+60%) rates. In this period, simulated north Icelandic water temperatures are at least 0.5 K warmer than average.